Post-obturation pain and its relationship with reference time and other risk factors - Alves, Ana Carolina Guimarães; Cabau, Leonardo; Pavan, Nair Narumi Orita; Tookuni, Izabela Volpato Marques; Viana, Bruna Angélica de Souza; Stulp, Patrícia; Pereira, Lucas Ferrari; Endo, Marcos Sérgio (Brazilian Dental Science, 2022)
Objective: To evaluate incidence and intensity of postoperative pain in patients treated in the Residency Program in Endodontics at the State University of Maringá. The influence of factors inherent to the patient and treatment on preoperative pain was also the focus of our study. Material and Methods: 99 patients participated in this study and underwent non-surgical endodontic treatment. Initially, palpation, vertical and horizontal percussion were performed on the tooth to be treated. After the root canals filling, patients received a printed Numerical Rating Scale and were instructed to record the level of pain in the postoperative periods of 24, 48 and 72 hours. For each postoperative period, the patient recorded the values. A descriptive analysis of the data and a model of generalized estimation equations were performed to verify the relationship between the variables and postoperative pain, at a significance level of 5%. Results: During the follow-up period, the pain rates found were low represented by 16%, 11% and 7% in the periods of 24, 48, and 72h, respectively. In addition, the rates significantly decreased after 72h. Only one case of flare-up was recorded. Presence of pain on palpation, use of reciprocating file and use of 2.5% sodium hypochlorite influenced the results (p<0.05), increasing the changes of post-operative pain by 3.36, 0.4 and 0.2 times, respectively. Conclusion: Incidence and intensity of postoperative pain monitored in the residency program reduced significantly after 72 hours. Postoperative pain was associated with pain on palpation, use of reciprocating files and irrigation with 2.5% hypochlorite. KEYWORDS Endodontics; Postoperative pain; Pain measurement; Endodontic treatment; Root canal therapy.